2022
DOI: 10.1111/eci.13888
|View full text |Cite
|
Sign up to set email alerts
|

An umbrella review and meta‐analysis of renin–angiotensin system drugs use and COVID‐19 outcomes

Abstract: Background: Despite the availability of extensive literature on the effect of angiotensin-converting enzyme inhibitors (ACEIs)/angiotensin-receptor blockers (ARBs) on COVID-19 outcomes, the evidence is still controversial. We aimed to provide a comprehensive assessment of the effect of ACEIs/ARBs on COVID-19-related outcomes by summarising the currently available evidence.Methods: An umbrella review was conducted using Medline (OVID), Embase, Scopus, Cochrane library and medRxiv from inception to 1 February 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 84 publications
0
7
0
2
Order By: Relevance
“…The results were in favor of the hypothesis that ACE I and ARB have protective effects in COVID-19 patients. The meta-analysis found that death and ICU admissions rates are lower in the study group [16].…”
Section: Discussionmentioning
confidence: 87%
“…The results were in favor of the hypothesis that ACE I and ARB have protective effects in COVID-19 patients. The meta-analysis found that death and ICU admissions rates are lower in the study group [16].…”
Section: Discussionmentioning
confidence: 87%
“…Benefits and risks of common medications used in metabolic syndrome management in the setting of COVID-19 are an area of intense research and discussion and have been reviewed in detail elsewhere [68] , [69] , [70] , [71*] , [72] , [73] . Data from meta-analyses [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , observational studies [25] and randomized controlled trials [84] , [85*] , [86] , [87] , [88*] , [89] have emerged while several studies are on-going. These are summarized in Table 2 .…”
Section: Preventing and Managing Covid-19 In People With Metabolic Sy...mentioning
confidence: 99%
“… Enhancing ACE2 expression – increases risk of viral entry, but decreases in inflammatory response [68] ↓mortality (MOB) b [76] - semaglutide [NCT04615871] DPP4 inhibitors Possible benefit through favourable immunomodulatory and anti-fibrotic effects [68] ↓ or ↔ mortality (MOB) b [78] ↓ mortality (MOB) b [78] linagliptin [NCT04542213], sitagliptin [NCT04365517] Insulin Possible harm through proinflammatory response and formation of reactive oxygen species [69] ↑mortality (MOB) b [77] - NCT04542213 (insulin vs linagliptin) Despite theoretical risks and observational data of harm, insulin remains the best option for glucose control in critically ill Statins Possible benefit through anti-inflammatory effects and limiting viral entry in to cells [70] ↓mortality (MOB) b [79] ↓mortality (MOB) b [82] [NCT04486508, NCT04631536., NCT04472611, NCT04904536] Continue during pandemic / acute infection – guided by standard cautions / contraindications Consider interactions with remdesivir / other antivirals [90] Omega-3 fatty acids Possible benefit through favourable immunomodulation [70] - ↓ symptoms and mortality (RCT) d [86] NCT04647604 Continue during pandemic / acute infection – guided by standard cautions / contraindications: Consider risks of: AKI with ACEI Major bleeding with aspirin ACEI/ARB Possible benefit through suppression of RAS activation. Increases ACE2 – benefit of anti-inflammatory effects of Ang-II likely to override the risk of facilitation of viral entry in to cells [71] ↓mortality (MOB) b [80] ↔ mortality & ↑ AKI (MCT) [83] , ...…”
Section: Preventing and Managing Covid-19 In People With Metabolic Sy...mentioning
confidence: 99%
“…Similarly, ARBs suppress the downstream immune responses and ameliorate acute lung injury [ 14 ]. In recent years, in spite of the extensive literature available on the effect of ACEIs/ARBs on COVID-19 outcomes, the evidence remains controversial [ 15 ]. However, among Chinese patients with hypertension hospitalized with CAP before 2019, the association of ARBs use with in-hospital mortality is also unknown well.…”
Section: Introductionmentioning
confidence: 99%